Initiating an Islamic Family in The Middle of the Rapid Flow of Globalization - Mufidah, Jariyah (International Conference of Moslem Society, 2018)
This paper aims to know and discuss the role of parents in the family, parenting and family functions in Islam. As we know, The development of today's technology is so rapidly advanced; users of digital tools are so mushrooming without knowing the age limit. The era of globalization is very influential for human life. In addition to presenting positive opportunities, it also offers the convenience provided by modernization. The information technology is very easy to access, but on the other side the negative effect of the rapid flow of globalization is increasingly felt and worrying. To filter and fortify it, the role of parents in the education of their children is required, especially moral education. Parents are required to play their role dynamically, democratically and communicatively on an ongoing basis.